Power TranformersS Diagnosis: Status Evaluation - Nogueira, Teresa Alexandra Ferreira Mourão Pinto; Quadrado, José Carlos; Felgueiras, Manuel Carlos Malheiro de Carvalho; Lopes, Carlos Silva (Neutro à Terra, 2021)
The reliability of the electrical grid depends on the availability and performance of crucial components such as power transformers. A failure in these expensive devices threatens supply energy warranty and system overhaul reliability. As transformers approach their end of life, the failure rate tends to increase and, therefore, both equipment diagnostics and working condition assessment are important to detect oncoming faults. In this work, we develop a state assessment methodology, able to evaluate power transformers health conditions. The study is about the transformer operation analysis and the associated status index calculation. This index value classifies the transformer general operation, according to the information of five partial indexes, reflecting the work conditions of most critical equipment: insulating oil and paper, winding and bushings. This contribution also presents an extensive transformer state analysis, backed up by in-service equipment.